LEARNER STRATEGIES FOR IMPROVING SPEAKING FLUENCY - MAMADJONOVA FERUZA (TADQIQOTLAR, 2025)
ABSTRACT Speaking fluency is a vital component of effective communication and a key goal in language learning. Learners often face challenges such as hesitation, lack of vocabulary, limited confidence, and poor pronunciation, which hinder their fluency development. This study explores various learner strategies for improving speaking fluency, including self-monitoring, shadowing, repetition drills, interaction with peers, and the use of digital tools. It also highlights the role of motivation, exposure to authentic materials, and consistent practice in enhancing fluency. The findings emphasize that adopting a combination of cognitive, metacognitive, and socio- affective strategies can significantly improve learners’ speaking performance. Encouraging autonomy, promoting meaningful interaction, and integrating technology-based practices are shown to be effective in fostering fluency.